(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2014)
Abstrak Pemilihan umum merupakan salah satu Peristiwa penting yang akan menentukan arah perjalanan sebuah negara. Ada 12 parti politik yang bertanding dalam pemilihan umum 2014. Pelaksanaan pemilihan umum tidak dapat dipisahkan dengan media,kerana media menjadi salah satu cara bagi parti politik untuk mendapatkan pemilih. Di Indonesia, hubungan antara politik dengan media menjadi lebih rumit kerana sebahagian besar ahli politik parti juga merupakan pemilik media massa nasional. Sudah menjadi sifat media, untuk selalu akan menyuarakan kepentingan pemiliknya. Namun, pada pemilihan umum 2014 ada fenomena yang menarik iaitu luasnya penggunaan media sosial, seiring dengan meningkatnya penggunaan internet di Indonesia. Maka, kempen politik bergeser dari ruang fizik menuju ruang maya. Jika pada pemilihan umum sebelum ini kempen politik selalu melibatkan massa yang besar, pawai atau orasi di tempat, terbuka, namun kali ini kempen yang dilakukan adalah lebih bersifat individu. Kempen dilakukan melalui telefon pintar, komputer riba dan gajet yang lain. Dengan media sosial, masyarakat bukan lagi penonton yang pasif tetapi aktif. Masyarakat boleh menjadi penyampai maklumat dan bukan hanya sebagai penonton, sehingga dominasi media massa konvensional runtuh. Salah satu fenomena yang menonjol adalah munculnya Tokoh Joko Widodo, yang popular dengan nama Jokowi, sebagai salah satu calon presiden dari Parti Demokrasi Indonesia Perjuangan. Jokowi berjaya menggunakan media sosial untuk bekempen, walaupun partinya tidak memiliki media massa. Abstract General election is one of the crucial moments that will determine the development of a country. There are 12 political parties competing in the 2014 Indonesian national elections. The elections cannot be separated with the media, because political parties use media in their campaign to influence voters. In Indonesia, the relationship between politics and the media becomes more complicated because most of the party’s political elites are also the owner of the national mass media. It is the nature of media, to always be voicing the interests of its owner. However, in the 2014 elections there is an interesting phenomenon: the increasing use of social media, along with the increasing penetration of the Internet in Indonesia. Thus, the political campaign shifted from physical space to the virtual space. If in the previous elections, political campaigns always involve huge masses and rhetorics in the open space; in this election the campaign carried more personal. Now, campaigns are conducted through smart phones, laptops and other gadgets. With social media, people are no longer passive but active audience. People can be a message producer and not just as an audience, so the conventional media dominance collapsed. One of the prominent phenomenon is the rising popularity of the president candidates from the Partai Demokrasi Indonesia Perjuangan, Joko Widodo, who is popularly known as Jokowi. Jokowi has successfully used social media for the campaign, even though his political party does not have the mass media.